The tax structure of an economy in crisis: Greece 2009-2017 - Chrysa Leventi; Fidel Picos (University of Essex, Institute for Social and Economic Research (ISER), 2019)
The 2010 Economic Adjustment Programme initiated a period of strict international supervision with respect to tax policy in Greece. The country implemented a large-scale fiscal consolidation package, aiming to reduce its public deficit below 3% of GDP by 2016. Since the beginning of the crisis, the provisions of the 'Greek Programme' have been revised several times, and personal income tax reform has figured prominently on almost each of the revision agendas. This paper aims to provide an assessment of the effects of the four major structural reforms that took place in Greece during and in the aftermath of the economic crisis; using microsimulation techniques, we simulate the (ceteris paribus) first-order impact of these reforms on the distribution of incomes, the state budget and work incentives, while also trying to identify the main gainers and losers of these policy changes. Our results suggest that all reforms had a revenue-increasing rationale, with the one of 2011 being designed to have the largest fiscal gains. The latter also strengthened redistribution and achieved the highest decrease in income inequality. The 2013 reform went to the opposite direction by reducing both the redistributive strength and the progressive nature of the Greek tax system. The striking discrepancies in the ways in which different household categories have been affected by the four reforms call for a deeper investigation of the possibility of moving towards more uniform personal income tax rules.
Keywords: H24; H23; I32; 330; personal income tax; reform; Greece; redistribution; work incentives